The Effectivenessof Subject Specific Pedagogy Based on Problem-Based Learning to Empower Student’s Ecological Literacy - Idhun Prasetyo Riyadi; Baskoro Adi Prayitno; Puguh Karyanto (LPMPP Universitas Negeri Yogyakarta, 2018)
Abstract:This study aims to determine the effectiveness of Subject Specific Pedagogy (SSP) based Problem-Based Learning (PBL) to empower the students' ecological literacy at Sebelas Maret University. This research was conducted on Biology Education Program of FKIP UNS. The research design used was posttest-only control design. The sample of the research is 6th semester student with the number of 46 as experiment class and 7th semester student with amount 57 as control class. The posttest value of ecological literacy for the experimental class was 80.77% while the control class was 68.14%. The result of posttest of ecological literacy questionnaire was analyzed using independent test of t-test. Result of t test is got sig value = 0,00 (0,05) so there is difference of ecological literacy between experiment class and control class. This difference is influenced by students who have or are receiving an ecology course in the semester. Therefore, PBL-based SSP tools produce different ecological literacy values in biology education students.Keywords: Subject Specific Pedagogy, Problem-Based Learning, effectiveness, Ecological LiteracyKeefektivan Subject Specific Pedagogy Berbasis Problem-Based Learning untuk Memberdayakan Ecological Literacy MahasiswaAbstrak: Penelitian ini bertujuan untuk mengetahui keefektivan Subject Specific Pedagogy (SSP) berbasis Problem-Based Learning (PBL) untuk memberdayakan literasi ekologi mahasiswa di Universitas Sebelas Maret. Penelitian ini dilaksanakan pada Program Studi Pendidikan Biologi FKIP UNS. Desain penelitian yang digunakan adalah posttest-only control design. Sampel penelitiannya merupakan mahasiswa semester 6 dengan jumlah 46 sebagai kelas eksperimen dan mahasiswa semester 7 dengan jumlah 57 sebagai kelas kontrol. Didapatkan nilai posttest literasi ekologi untuk kelas eksperimen sebesar 80,77% sedangkan kelas kontrol sebesar 68,14%. Hasil posttest kuisioner literasi ekologi dianalisis menggunakan uji beda dengan menggunakan independent t-test. Hasil uji t didapatkan nilai sig=0,00 (0,05) sehingga terdapat perbedaan literasi ekologi antara kelas eksperimen dan kelas kontrol. Perbedaan ini dipengaruhi oleh mahasiswa yang sudah atau sedang menerima mata kuliah ekologi di semesternya. Oleh sebab itu, perangkat SSP berbasis PBL menghasilkan perbedaan nilai literasi ekologi pada mahasiswa pendidikan biologi.Kata Kunci: Subject Specific Pedagogy, Problem-Based Learning, Keefektivan, Literasi Ekologi